A comparison of roots and affixes in Kurdish and English according to the Binding Theory - خضر, م.م. غفور عارف خضر; عبدالرحیم, آ.م.د. عثمان کریم عبدالرحیم (Sulaimani Journal for Humanities, 2025)
This paper, titled “Comparison of Anaphors and Pronouns in Kurdish and English According to Binding Theory”, explores the use of anaphors in pre-existing sources of the Kurdish language. Binding Theory, a part of the Government and Binding framework in Universal Grammar (UG), examines the relationship between anaphors, pronouns, and their antecedents within a sentence’s nominative structure. The theory consists of three principles: the first establishes a strict connection between pronouns and their antecedents, while the second and third principles describe relationships where pronouns are independent and unrestricted in reference. In both Kurdish and English, beyond personal pronouns, other linguistic elements—such as common, overt, and covert pronouns—can function similarly under the first two principles. Additionally, separate personal pronouns in both languages may either be directly linked to or remain independent of nominative components, especially in complex sentences. This linkage becomes particularly evident when pronouns in subordinate clauses connect to nominative elements in the main clause.
Keywords: clitics; anaphor; roots; Government and Binding Theory; Binding Theory